Metabolic syndrome correction in patients with non-alcoholic fatty liver disease and food behavior disorders - M. S. Yakovenko (Лечащий Врач, 2021)
242 patients with increase of body mass index were examined, of them, in 180 patients, fatty hepatosis was revealed. In the course of the examination, we defined manifestations of metabolic disorders in the patients: obesity, disorders in glucose tolerance, dislipidemy, arterial hypertension. In the course of treatment, in the experimental group, significant effects were achieved after application of ursodeoxycholic acid — hypolipidemic, weight loss, mostly pronounced in the application as a modifier of food behavior, psyllium preparation.